Development of Ethno-STEM Integrated Digital Teaching Material with Augmented Reality to Promote Students' 21st Century Skills - Aprina maharani ZAN; Asrizal (Postgraduate, University of Mataram, 2024)
Research into the development of Ethno-STEM integrated digital teaching materials is urgently carried out because of the enormous potential of this approach in holistically improving students' 21st century skills. Ethno-STEM combines local cultural values ​​with STEM concepts, creating a learning context that is relevant to students' everyday lives. The problem with this research is that students' 21st century skills scores are still in the low category, and the application of Information and Communication Technology (ICT) based teaching materials is also still low. The research solution is to develop integrated Ethno-STEM digital teaching materials assisted by Augmented Reality to improve students' 21st century skills. The research method is development research using the Ploomp model. Development research consists of 3 stages, namely the preliminary stage, development stage and assessment stage. The results of the research are that Etno-STEM integrated digital teaching materials have valid and practical criteria for use in physics learning. Ethno-STEM integrated digital teaching materials assisted by augmented reality are valid for aspects of material substance, learning design, visual communication and software utilization. Ethno-STEM integrated teaching materials assisted by Augmented Reality received practicality scores with good criteria in the aspects of useful, easy to use, interesting, clear, cost-effective and ETno-STEM.